Dependent convergence: the struggle to control petrochemical hazards in Brazil and the United States - Siqueira, Carlos Eduardo (Amityville, 2003)
"The international literature on the export or migration of hazards from developed to developing countries has mostly focused on the perspectives of exporting countries. The research reported here adds to that literature by studying the process of importation of petrochemical hazards and its controls by Cetrel, the waste-management company for the Camaçari Petrochemical Complex (located in Bahia, Brazil) from the perspective of the importers (Brazilian social actors). Based on initial evidence that indicated Cetrel’s long-term cooperation with the Gulf Coast Waste Disposal Authority (GCA), the waste management company for the Gulf Coast area of Texas, three case studies describe and analyze the process of importation: first, two benzene-related occupational and environmental health crises that affected the complex in the eighties; second, the environmental policies adopted by Cetrel; and third, the environmental policies carried out by the GCA. Comparative analyses of social actors and policy outcomes in Bahia and Texas show the similarities and differences in the actors and the policies adopted in each case. As a result of historical and structural developments in Bahia and Texas, Cetrel operates under pollution-control standards and technologies for protecting the environment and workers that are similar to those of the GCA. This convergent trend is characterized as dependent convergence between developing and developed countries. The author makes recommendations for stronger international solidarity among progressive forces in developed and developing countries to promote preventive alternatives to pollution control. "